Donor–acceptor naphthalimides and peryleneimides for all-solution-processed thin film lasers. Issue 42 (13th October 2022) - Donoso, Beatriz; Bonal, Víctor; Torres-Moya, Iván; Boj, Pedro G.; Quintana, José A.; Villalvilla, José M.; Herrera, Jesús; Prieto, Pilar; Díaz-García, María A.
Abstract : The potential of donor–acceptor naphthalimides and peryleneimides as laser dyes for all-solution processed thin film organic lasers is demonstrated through the observation of amplified spontaneous and distributed feedback laser fabrication. Abstract : Donor–Acceptor (D–A) naphthalimides (NI ) are highly fluorescent multitask compounds that have demonstrated success in a variety of optoelectronic applications, among which, thin film organic lasers (TFOLs) are not included. Here we assess the potential of various NI derivatives for lasing applications by investigating their amplified spontaneous emission (ASE) properties when dispersed in polystyrene thin films. To overcome the relatively low ASE photostability measured in the NI s, a series of peryleneimides (PI ) derivatives, with similar chemical structure but with more extended π-conjugation, is synthesized and reported here, together with a complete characterization of their optical and ASE properties, both in solution and thin film. Most investigated compounds show ASE, with emissions at different wavelengths spanning from the blue to the red, depending on the derivative. Furthermore, surface emitting TFOLs with top-layer polymeric distributed feedback resonators are fabricated and characterized. This work represents an advance in the field of low-cost TFOLs, by including two families of successful laser dyes, NI s and PI s, the latter with significantly better photostability.